2013
DOI: 10.1002/smll.201301915
|View full text |Cite
|
Sign up to set email alerts
|

High‐ versus Low‐Quality Graphene: A Mechanistic Investigation of Electrografted Diazonium‐Based Films for Growth of Polymer Brushes

Abstract: Electrografting using aryldiazonium salts provides a fast and efficient technique to functionalize commercially available 3-5 layered graphene (vapour-deposited) on nickel. In this study, Raman spectroscopy is used to quantify the grafting efficiency of cyclic voltammetry which is one of the most versatile, yet simple, electrochemical techniques available. To a large extent the number of defects/substituents introduced to the basal plane of high-quality graphene by this procedure can be controlled through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 64 publications
7
30
0
Order By: Relevance
“…After the third cycle, no further change in the Raman spectra was observed, indicating that the graphene surface was covered with monolayer of aryl groups in a good agreement with the observed saturation in CV Faradaic current data explained above. It is worth noting that the estimated defects density obtained using our method for three CV cycles was consistent with that reported for the grafting of carboxyphenyl tetrafluporoborate on graphene supported on SiO 2 using spontaneous electron transfer chemistry [32] as well as on Ni using the electrografting method in acetonitrile [39]. For graphene/Ni electrografting, five CV scans were shown to be necessary for realizing the maximal modification of the graphene surface.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…After the third cycle, no further change in the Raman spectra was observed, indicating that the graphene surface was covered with monolayer of aryl groups in a good agreement with the observed saturation in CV Faradaic current data explained above. It is worth noting that the estimated defects density obtained using our method for three CV cycles was consistent with that reported for the grafting of carboxyphenyl tetrafluporoborate on graphene supported on SiO 2 using spontaneous electron transfer chemistry [32] as well as on Ni using the electrografting method in acetonitrile [39]. For graphene/Ni electrografting, five CV scans were shown to be necessary for realizing the maximal modification of the graphene surface.…”
Section: Resultssupporting
confidence: 71%
“…The authors have demonstrated successful grafting of uniform thin films using electrochemistry and demonstrated modulation of graphene electronic properties by opening a band gap upon functionalization [38]. More recently, a mechanistic investigation of electrografted diazoniumbased films on few layers of graphene (vapordeposited) on nickel has been reported [39]. However, diazonium-functionalized monolayer CVD graphene sheets have not been applied to biosensing.…”
Section: Introductionmentioning
confidence: 97%
“…According to the specification from the supplier (i.e., Graphene Supermarket) Ni-Gra is composed of patches of 1-7 layers with dimensions of 3-10 mm. This is in accordance with Raman analysis carried out in a previous study [58]. With an average number of layers equal to 4, Ni-Gra should be considered as multilayer graphene [62].…”
Section: Evaluation Of the Quality Of Cvd-grown Graphene And Hopgsupporting
confidence: 74%
“…Because the measurements were carried out on a dried and therefore collapsed films, the refractive index of the layer was fixed at a constant value (real = 1.55; imaginary = 0), independent of the thickness. The average and the standard deviation values reported correspond to data points obtained from measuring three spots on each plate [58].…”
Section: Ellipsometrymentioning
confidence: 99%
See 1 more Smart Citation